Comparison of Giving Peppermint Aromatherapy and Lemon Aromatherapy Against Vomiting Nausea in Pregnant Women with Hyperemesis Gravidarum Level I - Yulia Herliani; Herni Kurnia; Ismah Khaerunisa (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2023)
According to WHO, symptoms of nausea and vomiting are experienced by around 70% of pregnant women in the first trimester. Management for nausea and vomiting can be pharmacological or non-pharmacological. One of the non-pharmacological treatments is peppermint aromatherapy and lemon aromatherapy which can overcome or eliminate nausea and vomiting. The purpose of this study was to compare the administration of peppermint aromatherapy and lemon aromatherapy to nausea and vomiting in pregnant women with Hyperemesis Gravidarum Level I in the Work Area of the Cigalontang Health Center in 2021. The research method is Quasy Experiment with two group pretest-posttest design. The samples in this study was 32 respondents with total sampling technique. Giving aromatherapy, both peppermint aromatherapy and lemon aromatherapy, is done by giving two drops of aromatherapy that the researcher bought with the brand